2011
DOI: 10.1002/bdd.747
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex is cleared rapidly and primarily unchanged via renal excretion

Abstract: Sugammadex is a modified γ‐cyclodextrin which rapidly reverses rocuronium‐and vecuronium‐induced neuromuscular blockade. Previous studies suggest that sugammadex is mostly excreted unchanged via the kidneys. This single‐center, open‐label, non‐randomized study used 14C‐labeled sugammadex to further investigate the excretion, metabolic and pharmacokinetic (PK) profiles of sugammadex in six healthy male volunteers. 14C‐labeled sugammadex 4 mg/kg (0.025 MBq/kg of 14C‐radioactivity) was administered as a single in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
0
38
0
1
Order By: Relevance
“…It acts by forming irreversible complexes at 1:1 ratio with free rocuronium molecules in the blood followed by elimination of sugammadex-rocuronium complex through renal excretion without any metabolization. 1,2 The recommended dose range for sugammadex is 2-16 mg/kg in humans, 3,4 however, doses up to 96 mg/kg has been used in a human tolerance study conducted by Peeters and colleagues. 5 They showed that sugammadex alone is well tolerated in a limited subject population of 13, with only 1 subject experiencing adverse effects attributable to sugammadex hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…It acts by forming irreversible complexes at 1:1 ratio with free rocuronium molecules in the blood followed by elimination of sugammadex-rocuronium complex through renal excretion without any metabolization. 1,2 The recommended dose range for sugammadex is 2-16 mg/kg in humans, 3,4 however, doses up to 96 mg/kg has been used in a human tolerance study conducted by Peeters and colleagues. 5 They showed that sugammadex alone is well tolerated in a limited subject population of 13, with only 1 subject experiencing adverse effects attributable to sugammadex hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at this time standard dosing continues to be based on weight and train of four twitches as outlined in the Hepatic metabolism is responsible for rocuronium and vecuronium clearance; renal clearance regulates the sugammadex-NMBA complex elimination. 10,[18][19][20][21][22][23][24] In healthy kidneys with a glomerular filtration rate (GFR) of 75-120 ml/min, 70% of the dose is excreted in six hours, and 80-90% in 24 hours. 21,25,26 In renal failure, with GFR <30ml/min, only 29% of the dose administered is cleared by 72 hours.…”
Section: Dosingmentioning
confidence: 99%
“…10,[18][19][20][21][22][23][24] In healthy kidneys with a glomerular filtration rate (GFR) of 75-120 ml/min, 70% of the dose is excreted in six hours, and 80-90% in 24 hours. 21,25,26 In renal failure, with GFR <30ml/min, only 29% of the dose administered is cleared by 72 hours. 24 The use of high-flux dialysis removes the bound sugammadex, but at this time sugammadex administration is not recommended for patients with severe renal dysfunction.…”
Section: Dosingmentioning
confidence: 99%
“…1,7 More than 90% of the dose is excreted within 24 hours, with 96% excreted in the urine. 1,9 Renal excretion (as unchanged drug) is the only observed route of elimination. No metabolism has been observed.…”
Section: Pharmacokineticsmentioning
confidence: 99%